Is there Any Correlation between Periodontal Diseases and Sleeping. - Nadia Mohammed Kadim1, Wasan LaftaAbdulla2, Suha Talal Abd3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background:Sleep deficiency has develop a worldwide occurrence, and epidemiologic facts show that little sleep period unfavorably influences human physical health. Essential methods include variation of immune-inflammatory mechanisms. These modifications possibly will donate to potentiation of critical periodontal disease.Aim of the study:The aim of this study was to assess if there was an relationship between periodontal diseases and sleeping in a sample of patients from the College of Dentistry.Materials and Method: Forty-Five subjects were sorted into 3 groups (n = 15 each) viz. clinically healthy, gingivitis and periodontitis. Periodontal status of subjects was evaluated by plaque index, gingival index and probing pocket depth. All the study subjects were managed Pittsburgh Sleep Quality Index (PSQI) questionnaire for the judgment of sleep deficiency.Results: Current study shown that the mean of PSQI was statistically non-significant for all all groups in this study which are: Healthy, Gingivitis and Periodontitis.Conclusion: This study with initial results is indicative of independent association of sleep deficiency with severity of periodontal disease, but certainly calls on for another studies in the future with larger samples number.